2017
DOI: 10.1007/s00438-017-1409-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of transcriptomic and metabolomic data reveals critical metabolic pathways involved in rotenoid biosynthesis in the medicinal plant Mirabilis himalaica

Abstract: Mirabilis himalaica (Edgew.) Heimerl is among the most important genuine medicinal plants in Tibet. However, the biosynthesis mechanisms of the active compounds in this species are unclear, severely limiting its application. To clarify the molecular biosynthesis mechanism of the key representative active compounds, specifically rotenoid, which is of special medicinal value for M. himalaica, RNA sequencing and TOF-MS technologies were used to construct transcriptomic and metabolomic libraries from the roots, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…All the results suggest that UV-B radiation improves the biosynthesis of rotenoid, a medicinal active ingredient of M. himalaica , which is mainly achieved by a series of regulatory activities induced by the PI signaling system and hormone signaling to promote the up-regulation of CHS . This result is consistent with previous studies that showed CHS is a key gene for rotenoid biosynthesis in M. himalaica [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…All the results suggest that UV-B radiation improves the biosynthesis of rotenoid, a medicinal active ingredient of M. himalaica , which is mainly achieved by a series of regulatory activities induced by the PI signaling system and hormone signaling to promote the up-regulation of CHS . This result is consistent with previous studies that showed CHS is a key gene for rotenoid biosynthesis in M. himalaica [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 94%
“…It is possible that the metabolic activities of M. himalaica are significantly enhanced under the UV-B radiation, and M. himalaica adapts to UV-B radiation by increasing the ultraviolet-absorbing substance. Rotenoid, an important medicinal active ingredient in M. himalaica , is one of the downstream products of flavonoid metabolism [ 58 , 59 ]. Previous studies on rotenoid have been focused extensively on its anti-cancer activity and the treatment of leukemia [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collision energy (CE) was 30 V (15 MS/MS events with a production accumulation time of 50 msec each). The parameters of the electron spray ionization (ESI) source were set as follows: ion source gas 1 as 60 psi, ion source gas 2 as 60 psi, curtain gas as 35 psi, source temperature 650°C, and ion spray voltage floating (ISVF) 5000 V or -4000 V in positive or negative mode, respectively [20, 21].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the transcriptomes throughout embryonic development of Strongylocentrotus purpuratus using RNA-seq were analyzed to understand the global gene regulatory networks during the embryonic development of sea urchins 17 ; a comparative transcriptome analysis of different colored tube feet in Strongylocentrotus intermedius was conducted to understand the differences at the molecular level and provide valuable information for marker-assisted breeding in this species 18 ; nuclear magnetic resonance (NMR)-based metabolomics was applied to embryos of the sea urchin Arbacia lixula to reveal the effects of decreased levels of choline and N-acetyl serotonin on the cholinergic and serotoninergic system 19 ; the metabolomic and de novo transcriptomic methods were used to investigate the reproductive success of the sea urchin Paracentrotus lividus which fed on two abundantly occurring benthic diatoms 20 . The integration of both metabolomics and transcriptomics is a powerful tool for revealing the biosynthetic mechanisms of key metabolic pathways 21 . Therefore, such studies can be used as an initial step to investigate the critical genes and the process of PUFA biosynthesis and metabolism in the sea urchin.…”
mentioning
confidence: 99%